TECHNICAL TRAINING FOR THE SPORT OF BASKETBALL AND THE ESSENCE OF ITS HISTORY - Nomozov Suyunbek Abdimalik oglu (Galaxy International Interdisciplinary Research Journal, 2021)
Due to various changes in the legislation on this sport, it has long been held differently in different countries. We are talking about the history of basketball and its rise in modern times.